MiR-300 regulates cellular radiosensitivity through targeting p53 and apaf1 in human lung cancer cells. Issue 20 (18th October 2017) - He, Jinpeng; Feng, Xiu; Hua, Junrui; Wei, Li; Lu, Zhiwei; Wei, Wenjun; Cai, Hui; Wang, Bing; Shi, Wengui; Ding, Nan; Li, He; Zhang, Yanan; et al.
ABSTRACT: microRNAs (miRNAs) play a crucial role in mediation of the cellular sensitivity to ionizing radiation (IR). Previous studies revealed that miR-300 was involved in the cellular response to IR or chemotherapy drug. However, whether miR-300 could regulate the DNA damage responses induced by extrinsic genotoxic stress in human lung cancer and the underlying mechanism remain unknown. In this study, the expression of miR-300 was examined in lung cancer cells treated with IR, and the effects of miR-300 on DNA damage repair, cell cycle arrest, apoptosis and senescence induced by IR were investigated. It was found that IR induced upregulation of endogenous miR-300, and ectopic expression of miR-300 by transfected with miR-300 mimics not only greatly enhanced the cellular DNA damage repair ability but also substantially abrogated the G2 cell cycle arrest and apoptosis induced by IR. Bioinformatic analysis predicted that p53 and apaf1 were potential targets of miR-300, and the luciferase reporter assay showed that miR-300 significantly suppressed the luciferase activity through binding to the 3′-UTR of p53 or apaf1 mRNA. In addition, overexpression of miR-300 significantly reduced p53/apaf1 and/or IR-induced p53/apaf1 protein expression levels. Flow cytomertry analysis and colony formation assay showed that miR-300 desensitized lung cancer cells to IR by suppressing p53-dependent G2 cell cycle arrest, apoptosis and senescence. These data demonstrate that miR-300 regulates the cellular sensitivity to IR through targeting p53 and apaf1 in lung cancer cells.